2022
DOI: 10.3389/fmed.2022.754979
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction (AMI) as the Effect Modifiers to Modify the Association Between Red Blood Cell Distribution Width (RDW) and Mortality in Critically Ill Patients With Stroke

Abstract: Background and ObjectivesFew studies have evaluated the impact of red blood cell distribution width (RDW) on prognosis for critically ill patients with acute stroke according to recent studies. The aim of this study was to investigate the association between RDW and mortality in these patients.MethodsClinical data were extracted from the eICU Collaborative Research Database (eICU-CRD) and analyzed. The exposure of interest was RDW measured at admission. The primary outcome was in-hospital mortality. Binary log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…28 Moreover, other studies have found that elevated RDW is linked to an unfavorable prognosis in AMI, and that the underlying mechanism may be related to chronic inflammation. [29][30][31] ALB is an essential protein in human plasma that helps maintain nutrition and osmotic pressure. In recent years, several studies have investigated the relationship between CRP and albumin levels, and they found that in inflammatory conditions, the CRP levels increase, while albumin levels decrease.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, other studies have found that elevated RDW is linked to an unfavorable prognosis in AMI, and that the underlying mechanism may be related to chronic inflammation. [29][30][31] ALB is an essential protein in human plasma that helps maintain nutrition and osmotic pressure. In recent years, several studies have investigated the relationship between CRP and albumin levels, and they found that in inflammatory conditions, the CRP levels increase, while albumin levels decrease.…”
Section: Discussionmentioning
confidence: 99%